Pricing behaviour under competition in the UK electricity supply industry (2009)
This paper investigates the evolution of electricity prices for domestic customers in the UK following the introduction of competition. The empirical analysis is based on a panel data set containing detailed information about electricity supply prices over the period 1999 to 2006. The analysis examines the pricing patterns and draws inferences concerning the benefits of incumbency and the gains from search. The econometric analysis of persistence and price dispersion provides rather limited support for the view that the market is becoming more competitive and also indicates that there remain significant potential benefits to consumers from searching alternative suppliers. © Oxford University Press 2009 All rights reserved.